Pembentukan Identitas Sosial Komunitas Hadhrami di Batavia Abad XVIII-XX - Ahmad Athoillah (Universitas Gadjah Mada, 2018)
This paper discusses the process of forming identities carried out by the Hadhrami community in Batavia throughout the late 18th century until the beginning of the 20th century. The taking of the topic was motivated by the strong social identity of the Hadhrami community in Batavia, especially in religion and economy since the 19th century to the present. The problem of this research is about the form and process of forming Hadhrami social identity from the end of the 18th century to the beginning of the 20th century. To answer these problems, a critical historical method is used by using various historical sources and relevant reference studies.Some of the results obtained from this study are various historical realities, such as the formation of social religious symbols including mosques and religious teaching forum. Some important things are the formation of economic identities such as wholesale trade, shipping businesses and property businesses. In addition, there were also shifting settlements from Hadhrami over the Koja people in Pekojan in the early 19th century, as well as the shift of the Hadhrami to the inland of Batavia in the late 19th century. These various realities ultimately affected various forms and processes of forming the social identity of the Hadhrami community, such as the material aspects, language, behavior, and collective ideas of the Hadhrami community especially at the beginning of the 19th century. Generally the Hadhrami community had transformed themselves and their collective parts into colonial society in Batavia until the beginning of the 20th century.